Pengaruh Suhu Pengeringan Elektroda E 7018 Terhadap Hasil Pengelasan Material A36 - Candra Wahyu Setyawan; Syaripuddin; Ahmad Lubi; Ferry Budhi Susetyo (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2022)
The better welding results are always a scientific challenge in welding engineering. This is to ensure the connection functions properly according to its designation. The main purpose of this study was to determine the effect of electrode drying temperature on the mechanical properties of ASTM A36 steel weld joint. This research was conducted at the Condet Welding Training Center and PT. Gamma Hepsi Condet. The tests carried out were visual tests, radiographs, and tensile tests. The results showed that the drying of the electrode E 7018 without an oven had a lot of welding defects on the inside in the form of porosity about 2 mm. The results showed that the highest tensile strength of 50.01 kgf/mm² was found in specimens using an electrode drying temperature of 230ºC.